Risiko Pembiayaan Pada Bank Syariah di Indonesia: Tinjauan Atas Pembiayaan Berbasis Bagi Hasil - Purwanto, Purwanto; Ramadani, M. Kevin; Fitriyani, Yeny (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2020)
This study aims to analyze how the role of profit-sharing based financing in minimizing non-performing financing at Islamic commercial banks in Indonesia. This type of research is a quantitative approach. The type of data used is secondary data in the form of quarterly periods March 2016-December 2018. Data analysis uses panel data regression analysis consisting of 9 Islamic commercial banks. The results of this study indicate that profit-sharing based financing, namely mudharabah, contributes to the decline in Non-Performance Financing. Meanwhile, profit-sharing based financing with a musyarakah contract contributed to the decline in non-performance financing, but not significantly.